THE EFFECT OF SOME CARBON SOURCES ON GROWTH PARAMETERS OF THE BEAUVRIA BASSIANA (BALS.)VUILL - Diwan, Hussein; Khamas, Muna (Iraqi Journal of Science, 2024)
Seven carbon sources; Glucose,Sucrose,Soluble starch,Pectine,Dibis,Wheat seedsextract and Rice grains extract extract individually incorporated in different liquidmedia were evaluated for their effects on sporulation,percent of spores germinationand fungal biomass dry weight of entomopathogenic fungus Beauveria bassiana forfour incubation periods ;1,2,3 and 4days at 28±1c. Carbon used in the basal mediumas 8g/l.The results showed that glucose,rice grains extract,wheat seeds extract weresignificantely superior(p<0.05) to induce the fungal sporulation which recorded67,69,68×10 5spore/ml after 4 days of incubation, respectively.Soluble starch was more efficiency for spores germination,whereas the percent of spores germinationwas 24.3 after 4 days of incubation. Rice grains extract increased significantly thedry weight of fungus which recorded 0.507g/ml after 4days ofincubation.Pectine,soluble starch,sodium nitrate,methionin and glycin were lessefficiency for biomass production(0.2g/50ml).